2015
DOI: 10.1021/acssuschemeng.5b00580
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of a Renewable Pressure-Sensitive Adhesive System Derived from ε-Decalactone, l-Lactide, Epoxidized Soybean Oil, and Rosin Ester

Abstract: Pressure-sensitive adhesives (PSAs) are prepared with plant-based thermoplastic polyester elastomers (TPPEs), rosin ester tackifier, and epoxidized soybean oil plasticizer. Controlled bulk ring-opening transesterification polymerization of ε-decalactone and L-lactide using diethylene glycol as an initiator gives ABA type block polyesters via a onepot, two-step process with only tin(II) ethylhexanoate. Three semicrystalline poly(L-lactide)−poly(ε-decalactone)−poly(Llactide) (PLLA−PDL−PLLA) triblock copolymers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
121
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(130 citation statements)
references
References 58 publications
3
121
0
Order By: Relevance
“…The thermal degradation of MBM also was characterized in air flow, and the thermal stability was much lower, with a 5% degradation temperature of 285 °C ( Figure S7 ). Furthermore, when comparing SaBSa to other model bioinspired PSAs reported in the literature, the lignin-derived materials herein have thermal degradation temperatures in air that are at least 30 °C higher than acrylate-functionalized glucose, acrylate-functionalized isosorbide, and polyester-based systems, 38 , 39 , 42 providing a much larger temperature window for processing.…”
Section: Resultsmentioning
confidence: 99%
“…The thermal degradation of MBM also was characterized in air flow, and the thermal stability was much lower, with a 5% degradation temperature of 285 °C ( Figure S7 ). Furthermore, when comparing SaBSa to other model bioinspired PSAs reported in the literature, the lignin-derived materials herein have thermal degradation temperatures in air that are at least 30 °C higher than acrylate-functionalized glucose, acrylate-functionalized isosorbide, and polyester-based systems, 38 , 39 , 42 providing a much larger temperature window for processing.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the performance of TPEs have been significantly improved by inducting self‐healable properties, stimuli‐responsive properties and tunable morphology . In addition, environment‐friendly TPEs have also been successfully developed using sustainable and renewable resources . These strategies to develop new types of linear TPEs are also expected to advance the design and synthesis of multigraft TPEs.…”
Section: Resultsmentioning
confidence: 99%
“…According to Miao et al , the biocompatibility of polyurethane using a lactic acid initiator was tested in mice, and cell proliferation was confirmed on polyurethane. Polyurethane made from plant oil based 10‐Undecenoic acid is also known to be biocompatible . Gonzalez‐Paz et al reported that the polyurethane made by polymerizing the diol prepared by linking a hydroxyl group to a double bond and the carboxyl group of 10‐undecenoic acid and the 4,4’‐ethylenebis(phenylisocyanate) was found not to be biotoxic.…”
Section: C3–c30 Oil Derivativesmentioning
confidence: 99%